1991
DOI: 10.2135/cropsci1991.0011183x003100010022x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Reduced Palmitic Acid Content in Seed Oil of Soybean

Abstract: Reduction of the palmitic acid content of soybean [Glycine max (L.) Merr.] would lower the total saturated fatty acid content of the seed oil. A mutant line, A1937NMU‐173, with ≈30 g kg‐1 less palmitic acid than commercial soybean cultivars was obtained by the treatment of seeds of the cultivar A1937 with N‐nitroso‐N‐methyl‐urea (NMU). To determine the genetic control of the reduced palmitic acid, A1937NMU‐173 was crossed reciprocally to C1726, a line with the fap1 allele that lowers the palmitic acid content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 0 publications
2
81
0
1
Order By: Relevance
“…B019 was a line with NP and reduced palmitate developed jointly by Iowa State University and Pioneer Hi-Bred International, Inc. The reduced-palmitate trait in B019 was controlled by the recessive alleles/api and fap 3 (Fehr et al, 1991). A total of 20 BCiF 2 -derived lines that had LP and reduced-palmitate and 20 lines that had NP and reduced-palmitate were evaluated at three Iowa locations in 2003.…”
Section: Influence Of Low Phytate On Agronomic and Seed Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…B019 was a line with NP and reduced palmitate developed jointly by Iowa State University and Pioneer Hi-Bred International, Inc. The reduced-palmitate trait in B019 was controlled by the recessive alleles/api and fap 3 (Fehr et al, 1991). A total of 20 BCiF 2 -derived lines that had LP and reduced-palmitate and 20 lines that had NP and reduced-palmitate were evaluated at three Iowa locations in 2003.…”
Section: Influence Of Low Phytate On Agronomic and Seed Traitsmentioning
confidence: 99%
“…CXI834, the donor of the phal and pha2 alleles, was obtained from the USDA-ARS and Purdue University. B019 was a line homozygous for ihefapl and fap3 alleles for reduced palmitate that was developed jointly by Iowa State University and Pioneer Hi-Bred International, Inc (Fehr et al, 1991 The desired genotype was Phal phal Pha2pha2 because it was the only one that could produce LP BCiF 2 progeny. Eleven seeds from each BCIFI plant were analyzed to identify those that had at least one LP seed, which indicated that the plant had the Phal phal Pha2pha2 genotype.…”
Section: Line Developmentmentioning
confidence: 99%
“…Several lines with reduced palmitic acid concentration were developed by ethyl-methyl sulfonate mutagenesis (C1726, homozygous for the fap1 allele and ELLP2, homozygous for the fap * or fapx alleles); N-nitroso-Nmethyl urea mutagenesis (A22, homozygous for the fap3 allele); and X-radiation (J3 homozygous for the sop1 allele) (Fehr et al 1991;Stojšin et al 1998;Wilcox and Cavins 1990;Rahman et al 1996). In addition, one natural mutation (fap nc ) was discovered in line N79-2077-11 and its sister line N79-2077-12, both derived from the fifth cycle of a recurrent selection program for high oleic concentration (Burton et al 1983;Burton et al 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…The fapl and fap3 alleles were independently developed by treatment of seeds of commercial soybean cultivars with chemical mutagens (Erickson et al, 1988;Fehr et al, 1991). Genotypes homozygous for the two alleles have about 40 g kg-1…”
mentioning
confidence: 99%